Perlindungan Hukum Dalam Pemberian Upah Dan Peningkatan Kesejahteraan Buruh Non-Kontrak Di Aria Mebel Surakarta - Agustin, Lusiana Dewi, Shalman Al Farizi, S.H., M.Kn (2017)
This study aims to determine wages in Aria Furniture Surakarta is appropriate or not to the minimum wage and income to determine the effort to improve the welfare of workers in providing legal protection under Act No. 13 of 2003 on Manpower. This research method using empirical juridical approach with primary data in the form of interviews and secondary data from the materials library. Data were collected by literature study and field study using qualitative data analysis. The results of the study at Aria Furniture wages according to the minimum wage is not sufficient. Efforts to improve the welfare of workers by providing failitas welfare and protection of the right.